2013
DOI: 10.1016/j.ijsp.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Overtightening of halo pins resulting in intracranial penetration, pneumocephalus, and epileptic seizure

Abstract: A 60-year-old man sustained an undisplaced type III odontoid fracture following a fall down a full flight of stairs. His medical history was remarkable for a partial pancreatectomy and splenectomy in 2006 for chronic pancreatitis. This had rendered him diabetic, on insulin, and he required long-term administration of penicillin V.The fracture was treated with a halo vest, and, unknowing of its potentially serious consequences, the patient continued to tighten the halo pins himself.He presented 1 month later fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…Overtightening of halo pins may cause intracranial penetration, pneumocephalus, and epileptic seizure. 15,16 Intracranial abscess has also been reported. 17 Our study noted 3 patients with thoracic skin ulcers and 2 with severe prolonged swallowing problems after halo application (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Overtightening of halo pins may cause intracranial penetration, pneumocephalus, and epileptic seizure. 15,16 Intracranial abscess has also been reported. 17 Our study noted 3 patients with thoracic skin ulcers and 2 with severe prolonged swallowing problems after halo application (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…The complications associated with its use have been well described in the literature. [ 11 12 13 14 15 16 ] Particularly in the elderly, its use is associated with increased incidence of pneumonia and increased mortality. [ 4 17 18 ] More recent reports have challenged this,[ 3 16 19 ] but it remains a concern for the clinician.…”
Section: Discussionmentioning
confidence: 99%
“…Facial scarring at the site of pin insertion is another distressing problem. Glover et al reported penetrative skull and dural injuries, epilepsy, and pneumocephalus due to the overtightening of the halo pins by the patient (13). Therefore, CH usage needs proper patient education and close monitoring.…”
Section: Discussionmentioning
confidence: 99%